The ‘Utilitarian-Anxiety Paradox’: A TAM-based Analysis of Junior High School English Teachers’ Artificial Intelligence Acceptance - Faisal Faisal; Maulida Qurrota A'yunina; Condro Nur Alim; Jiraporn Yiamkhamnuan (FKIP Universitas Lampung, 2026)
Despite the widespread perception that artificial intelligence (AI) has the potential to transform English teaching, the psychological dimension of teachers’ acceptance, particularly the coexistence of high perceived usefulness and persistent anxiety, remains under-theorized in the Indonesian junior-secondary context. Using the Technology Acceptance Model (TAM), this study aimed to (1) determine the level of AI acceptance among junior high school English teachers in Indonesia and (2) investigate the factors shaping it, especially the proposed ‘utilitarian-anxiety paradox.’ In a quantitative cross-sectional survey, 42 teachers completed a Likert-scale instrument derived from Wang et al. (2021), measuring six TAM constructs: perceived usefulness (PU), perceived ease of use (PEU), self-efficacy (SE), anxiety (AN), attitude toward use (ATU), and behavioral intention (BI). Data were analyzed using descriptive statistics, Pearson correlations, multiple linear regression, and a moderation analysis. Overall acceptance was high (M = 3.96), with PU (M = 4.32) and BI (M = 4.08) rated most positively. At the same time, anxiety remained moderate (M = 3.54), and analysis showed that anxiety did not decrease with teacher perception of AI as more useful or easier to use. A multiple linear regression model explained 70.6% of the variance in behavioral intention (R² = .706, p < .001); emotional comfort (reverse-scored anxiety) was the strongest predictor (β = .427), followed by PU (β = .366) and SE (β = .334). In contrast, PEU was not significant (β = -.105). Although anxiety did not significantly moderate the usefulness–intention relationship overall (p = .13), a simple-slopes analysis indicated that perceived usefulness mattered most when teacher anxiety was high. These findings provide evidence for a ‘utilitarian-anxiety paradox,’ suggesting that positive usability perceptions do not fully account for teachers’ emotional readiness to adopt AI, and call for context-sensitive professional development to build digital resilience in Indonesian secondary settings. Keywords: artificial intelligence acceptance, english teachers, junior high schools.